An Analysis of Juvenile Delinquency in Lauren Oliver’s vanishing girls novel: An Analysis of Juvenile Delinquency in Lauren Oliver’s vanishing girls novel - pohan, annisaoktriulinah (Center of Language and Cultural Studies [CLCS], 2023)
This thesis is titled